Patrons of Women Literacy Projects and Gender Development in Rural Nepal - Hertzog, Esther (Berghahn Books, 2011)
Assuming women's empowerment would accelerate the pace of social change in rural Nepal, the World Bank urged the Nepali government to undertake a "Gender Activities Project" within an ongoing long-term water-engineering scheme. The author, an anthropologist specializing in bureaucratic organizations and gender studies, was hired to monitor the project. Analyzing her own experience as a "development expert," she demonstrates how the professed goal of "women's empowerment" is a pretext for promoting the interests of local elites. She demonstrates how a project intended to benefit women fails to provide them with any of the promised resources.